Reactivity of platinum(II) triphenylphosphino complexes with nitrogen donor divergent ligands. (24th November 2016) - Belli Dell' Amico, Daniela; Bellucci, Luca; Labella, Luca; Marchetti, Fabio; Samaritani, Simona
Graphical abstract: Cis -[PtCl2 (PPh3 )(NCMe)] reacted with N–N divergent bidentate nitrogen ligands in a Pt/N–N molar ratio 2 or 1, affording dinuclear or mononuclear complexes. Two dinuclear trans, trans- products, a cis, cis- one, and a mononuclear phosphane adduct were structurally characterized. Equilibria were observed in solution, involving ( trans – trans )-[PtCl2 (PPh3 )2 (μ-N–N)], trans - and cis -[PtCl2 (PPh3 )(N–N)] and free N–N. Abstract: Dinuclear platinum(II) complexes [PtCl2 (PPh3 )2 (μ-N–N)], where N–N is a divergent bidentate nitrogen ligand, were prepared by reacting cis -[PtCl2 (PPh3 )(NCMe)] with N–N in a Pt/N–N molar ratio 2. The ( trans, trans )-isomers were obtained as kinetic products and recovered in good yields and high purity 1, N–N = pyrazine (pyrz);2, N–N = 4, 4′-bipyridyl (bipy);3, N–N = piperazine (pipz);4, N–N = p-xylylendiamine (xylN2 ). Cis -[PtCl2 (PPh3 )(NCMe)] was also reacted with the tridentate divergent ligand 2, 4, 6-tris-(pyrid-4′-yl)1, 3, 5-triazine (py3TRIA) in molar ratio 3 with formation of the trinuclear ( trans, trans, trans )-[PtCl2 (PPh3 )3 (μ-py3TRIA)], 5 . On the other hand, the treatment of cis -[PtCl2 (PPh3 )(NCMe)] with the monodentate pyridine (py) produced a mixture of both trans -[PtCl2 (PPh3 )(py)] (6a ) and cis -[PtCl2 (PPh3 )(py)] (6b ). The reactions of cis -[PtCl2 (PPh3 )(NCMe)] with N–N = pyrz, bipy, pipz, carried out with a Pt/N–N molar ratio 1, were monitored by 31 P NMR spectroscopy. Equilibria were observed in solution, involving dinuclear ( trans – trans )-[PtCl2 (PPh3 )2 (μ-N–N)], mononuclear [PtCl2 (PPh3 )(N–N)] and free N–N. The addition of an excess of the divergent ligand allowed the complete conversion to the corresponding mononuclear complexes. With the heteroaromatic ligands both geometric isomers were observed (7a, 7b and8a, 8b, for pyrz and bipy derivatives, respectively) while with pipz the trans -isomer only was detected, 9 . In the system involving bipy, the scarcely soluble dinuclear ( cis, cis )-[PtCl2 (PPh3 )2 (μ-bipy)], 2b, was also obtained. Products2, 2b, 3 ·2(CHCl3 ) and6a ·0.5(C2 H4 Cl2 ) were structurally characterized by single crystal X-ray diffraction methods.